PENGEMBANGAN TES KEMAMPUAN PEMECAHAN MASALAH PADA ISU PENCEMARAN LINGKUNGAN - Ilena Amalia Luthfi; Dewi Robiatun Muharomah; Rizhal Hendi Ristanto; Mieke Miarsyah (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2019)
The ability to solve problems is one of the skills by students in the 21st century. The problem that is often discussed and still unsolved is environmental issues. Environmental issues are required to be included in every school subject, so that students care more about what happens in the environment. Appropriate assessment is useful for developing students' abilities. The purpose of this study was to develop an instrument of problem solving ability at the junior high school level. The research method used is modification of the research and development model Borg and Gall. This research is limited to testing the feasibility of the instruments developed. The results showed an average validity test by peer validator of 3.70 with very valid categories and 13 valid items based on Pearson product moment and had high reliability. The conclusion of this study is that the instruments developed are suitable to be used as evaluation of learning for students at the junior high school level.